Ionic Liquid Screening of Octachlorodibenzo-P-Dioxin Captured from Water Samples by σ-profile Analysis for Microextraction Applications - Romero-Figueroa, J; Quijada-Maldonado, E; Araya-Lopez, C; Olea-Chandia, F; Villarroel-Utreras, E (Elsevier B.V., 2022)
The extraction of octachlorodibenzo-p-dioxin (OCDD) is very challenging due to its highly non-polar nature, demanding the use of large amounts of toxic solvents. Ionic Liquids (ILs) for OCDD extraction were screened to replace traditional solvents using the Conductor-like Screening MOdel for Real Solvents (COSMO-RS). The analysis was performed by studying the σ-profile of a variety of commercially available cations and anions employed in the literature. The effects of different alkyl chain lengths and configurations were studied in cations. In the case of anions, different reported structures, including fluorine- or oxygen-bearing structures, were assessed. Results indicate that the alkyl chain, symmetry, and nature of the central atom in the cations are critical factors to achieve high affinity to OCDD. The polarity of anions was found to be modified by adding highly electronegative atoms, a steric hindrance to the central atom and the use of planar geometries with symmetrical groups. The performance of ILs for extracting OCDD was compared with that of conventional solvent extractants used for quantifying dioxins in the US EPA-1613 method. Finally, three cations and anions are proposed as candidates for dioxin extraction. © 2022